Has the COVID-19 Pandemic Reshaped Non-Cash Payments in Indonesia? - Khaliq, Abdul; Karimi, Syafruddin; Taifur, Werry Darta; Ridwan, Endrizal (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
This paper aims to quantify whether the COVID-19 pandemic has reshaped Indonesia’s non-cash payments (NCP). Covering monthly real-time gross settlement (RTGS) of NCP data published by the Bank of Indonesia spanning the period 2009M01–2023M06, we explore the effect of the COVID-19 pandemic from March 2020 to June 2023 on NCP by implementing the Newey-West experiment of ITSA. The empirical results reveal that the ITSA precisely measures the COVID-19 pandemic impact on NCP transactions. The effect of the pandemic has varied on transaction volume using various proxies of NCP in Indonesia. The pandemic had a significant positive effect on electronic money in the first month. After that, however, the pandemic negatively affected total debit and credit card transactions. The trend of NCPs postCOVID-19 pandemic has been increasing, supported by positive trends in almost all selected sub-components of NCP except inter- and intrabank debit card transactions. These estimation results indicate that Indonesia’s central bank should intensively innovate different NCP instruments of the payment system policy toward a non-cash society, especially post-pandemic.